The Effect of the Covid-19 Free Operation Path Protocol on the Incidence of Lung Complications in Postoperative Elective Patients at dr. Moewardi Hospital Surakarta - Galih Aktama; Henky Agung Nugroho; Muhammad David Perdana Putra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
The pandemic that began in late 2019, COVID-19, affects all patients, including cancer patients. Patients with cancer that continues to spread and there is no other effective alternative treatment must undergo surgery so that cancer does not get worse. Given this problem, many health care centers have developed a protocol system in the form of a COVID-19-free surgical route. This study is a retrospective cohort study comparing the incidence of pulmonary complications in patients undergoing elective cancer surgery at dr. Moewardi Surakarta before and during the COVID-19 pandemic. The study sample was adult patients aged ≥ 18 years which underwent elective surgical procedures with the aim of curative cancer starting before COVID-19 (March 2019-February 2020) until the time the COVID-19 pandemic emerged (March 2020 - February 2021). The data obtained were 768 patients. Of these patients, 384 were classified as having a COVID19-free operation route during the pandemic, and 384 others underwent elective surgery in the pre-pandemic period. Based on the Chi-Square test, a p-value of 0.850 was obtained (P>0.05) which shows that there is significant difference between cases of pulmonary complications in surgical patients before and after the pandemic who were carried out through the COVID-19-free protocol route. In conclusion, there is no significant change in effect of the covid-19 free operation path protocol on the incidence of lung complications in postoperative elective patients at dr. Moewardi Hospital Surakarta, although this patented and mandatory protocol can reduce cancer patients’ morbidity and mortality who undergoing elective surgery during a pandemic.